The teacher's funeral a comedy in three parts - Peck, Richard (Dial Books, 2004)
In rural Indiana, in 1904, fifteen-year-old Russell's dreams of quitting school and joining a wheat-threshing crew are disrupted when his older sister takes over the teaching of his one-room school house after mean old Myrt Arbuckel "hauls off and dies."